PENGARUH FUNGSI KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PERSONIL SATLANTAS DI POLRESTABES BANDUNG - YONO . (Magister Manajemen Pascasarjana Universitas Langlangbuana, 2022)
The purpose of this study is to see how the leadership function and organizational culture affect on Satlantas Personnel’s Performance at Bandung Polrestabes.This is a quantitative study with such a questionnaire as the data source. It uses descriptive and verification analysis methods. The population in this study was 50 people who were personnel of the Bandung Polrestabes Police Satlantas. The analysis technique used is path analysis and partial hypothesis testing (t test) and simultaneous test (f test). According to the results of partial and simultaneous testing, the variables of leadership function and organizational culture have a substantial impact on Satlantas Personnel’s Performance at Bandung Polrestabes.This means that if the leadership function and the implementation of a good organizational culture are improved further, Satlantas Personnel’s Performance at Bandung Polrestabes will improve. Keywords : Leadership Function, Organizational Culture and Performance